Filtering Konten Negatif Menggunakan Metode Algoritma C4.5 dan API Bing Penerapan di Desa Kelet - Ahmad Faidlon; Muhammad Miftakhul Ulum; Muhammad Nabil Mas’ud; Fabelo Adi Putra Pradana; Ibnu Maulana (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
A search engine is a tool used to find on the internet by entering the desired key words or phrases, for example if you search for information about cars with information using a search engine, you will get results in the form of a list of websites that contain information about cars. Search engines are very useful because they allow you to find the information you need quickly and easily. This will be even better if a word/keyword filtering system is combined which is used to filter words or phrases to promote local products. Word filters can also be used to avoid the use of inappropriate words or phrases in a particular context. In this research, I used the API from Bing to get data. The results of this research are in the form of a web application that can filter keywords entered by the user, the keywords that have been input are filtered and if there are dirty words then these words will be deleted, after filtering the keywords it will then proceed to the Bing API for search for articles that can be read by users.